2022
DOI: 10.1111/1747-0080.12764
|View full text |Cite
|
Sign up to set email alerts
|

A review of the growth and development of Australian practice nursing: Insights for the dietetic workforce

Abstract: Aim The aim of this scoping review was to provide an overview of the development of practice nurses, and the learnings that could be applied to improve the profile of dietetics practice in primary care. Methods A scoping review synthesising peer‐reviewed and other literature relevant to the development of Australian practice nurses was conducted. Structured searches using keywords ‘general practice’, ‘nurse’ and ‘Australia’ were conducted in PubMed and Google Scholar in June 2021. Key government websites, Depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Participants called for more guidance on a standardised approach to using satisfaction measures in practice, echoing recent calls by Davidson and Reidlinger. 35 Dietitians recognised that their current software limits the integration and usability of data, and calls were made for a more uniform approach in software development. This has been documented by others 36 and is consistent with the World Health Organisation's call for Governments to introduce national health information technology standardisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants called for more guidance on a standardised approach to using satisfaction measures in practice, echoing recent calls by Davidson and Reidlinger. 35 Dietitians recognised that their current software limits the integration and usability of data, and calls were made for a more uniform approach in software development. This has been documented by others 36 and is consistent with the World Health Organisation's call for Governments to introduce national health information technology standardisation.…”
Section: Discussionmentioning
confidence: 99%
“…Dietitians in this study identified that most of the 45 evidenced‐based business standards are feasible to implement but called for more formalised business training or mentorship to enable that to happen. This finding has been recognised by others previously 8,35 and may have implications for tertiary dietetic institutes and the accrediting bodies that govern them. The six business standards with ‘Poor’ or ‘Fair’ feasibility related to either client or referrer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation